IMPLEMENTASI KURIKULUM MERDEKA PADA PROGRAM KEAHLIAN MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS: STUDI KASUS DI SMK NEGERI 9 SEMARANG - Charen Charen; Ahmad Saeroji (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The implementation of the Merdeka Curriculum in Vocational High Schools (SMK) represents a significant transformation in Indonesia's national education system. This study aims to describe the implementation of the Merdeka Curriculum in the Office Management and Business Services (MPLB) program at SMK Negeri 9 Semarang, identify supporting and inhibiting factors, and analyze teacher and student responses. A qualitative descriptive approach was employed with data collected through in-depth interviews, non-participant observation, and documentation. Informants comprised the Vice Principal for Curriculum, two productive subject teachers, and six Grade XII students. Findings reveal that SMK Negeri 9 Semarang has implemented the Merdeka Curriculum since 2022/2023 using a phased approach, integrating Project-Based Learning (PBL) and the Deep Learning pedagogical approach across all subjects. Two P5 co-curricular projects were implemented: batik ciprat making (Class X, 180 JP, 359 students) and a digital campaign on waste management (Class XI, 144 JP, 355 students). Supporting factors include institutional training, the Skandilan learning community, university and industry partnerships, and ICT facilities. Inhibiting factors include heavy teacher workloads, time management challenges in PBL, and technology adaptation difficulties among senior teachers. Students responded positively, recognizing that PBL is more engaging and relevant to workplace experience. These findings contribute empirical evidence on Merdeka Curriculum implementation in the Office Administration field. ABSTRAK Implementasi Kurikulum Merdeka di Sekolah Menengah Kejuruan (SMK) merupakan transformasi besar dalam sistem pendidikan nasional Indonesia. Penelitian ini bertujuan mendeskripsikan implementasi Kurikulum Merdeka pada Program Keahlian Manajemen Perkantoran dan Layanan Bisnis (MPLB) di SMK Negeri 9 Semarang, mengidentifikasi faktor pendukung dan penghambat, serta menganalisis respons guru dan siswa. Penelitian menggunakan pendekatan kualitatif deskriptif dengan data dikumpulkan melalui wawancara mendalam, observasi nonpartisipan, dan studi dokumentasi. Informan terdiri dari Waka Kurikulum, dua guru produktif MPLB, dan enam siswa kelas XII. Hasil menunjukkan bahwa SMK Negeri 9 Semarang mengimplementasikan Kurikulum Merdeka sejak 2022/2023 secara bertahap, mengintegrasikan Project-Based Learning (PBL) dan pendekatan Pembelajaran Mendalam (Deep Learning) di seluruh mata pelajaran. Dua proyek kokurikuler P5 dilaksanakan: pembuatan batik ciprat (kelas X, 180 JP, 359 siswa) dan kampanye digital pengelolaan sampah (kelas XI, 144 JP, 355 siswa). Faktor pendukung meliputi pelatihan institusional, komunitas belajar Skandilan, kemitraan DUDI dan perguruan tinggi, serta fasilitas teknologi. Faktor penghambat mencakup beban kerja guru, manajemen waktu PBL, dan adaptasi teknologi guru senior. Siswa merespons positif karena PBL lebih menarik dan relevan dengan pengalaman kerja.